2019
DOI: 10.1002/dev.21908
|View full text |Cite
|
Sign up to set email alerts
|

Early life stress sensitizes individuals to the psychological correlates of mild fluctuations in inflammation

Abstract: Background Early life stress (ELS) has been linked to health disparities across the human lifespan, particularly increased risk for depression and its recurrence. In this study we explore two plausible and competing pathways through which ELS may lead to depression via inflammation. Methods Participants (ages 18–22; n = 41) completed the Early Trauma Inventory as a measure of ELS. Participants then completed consecutive daily diaries of mood and other sickness behavior for the 7 days prior to and 7 days after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 67 publications
3
27
0
Order By: Relevance
“…For example, the longitudinal ACE cohort study found that proinflammatory proteins CRP and IL-6 moderated the association between prior stressful events and depression at follow-up [90]. Early life adversity may also interact with inflammation, with 6 [66,97,[103][104][105]132] of 7 studies showing that early life adversity is strongly associated with inflammation in young people, particularly CRP; however, this association was often independent of depressive symptoms. These findings are consistent with a meta-analysis in adults on the effect of early life trauma on inflammation, in which higher CRP, IL-6 and TNF-α was found, suggesting long-lasting effects [133].…”
Section: Study Design and Sample Selectionmentioning
confidence: 99%
“…For example, the longitudinal ACE cohort study found that proinflammatory proteins CRP and IL-6 moderated the association between prior stressful events and depression at follow-up [90]. Early life adversity may also interact with inflammation, with 6 [66,97,[103][104][105]132] of 7 studies showing that early life adversity is strongly associated with inflammation in young people, particularly CRP; however, this association was often independent of depressive symptoms. These findings are consistent with a meta-analysis in adults on the effect of early life trauma on inflammation, in which higher CRP, IL-6 and TNF-α was found, suggesting long-lasting effects [133].…”
Section: Study Design and Sample Selectionmentioning
confidence: 99%
“…These responses, either directly or via interaction with the social environment, can cause alterations in biological functioning that include the onset of chronic low-grade inflammation, which can increase risk for sickness behaviors, infections, mental and physical health problems, and premature mortality in vulnerable individuals (26,(47)(48)(49). Consistent with this thinking, several lines of evidence indicate that stressful life events are strongly associated with altered immune function and the development of depression, especially for persons living in a high-risk environment (e.g., trauma exposure) who possess a genetic predisposition to depression (20,(50)(51)(52). Moreover, clinical studies have shown that depressive symptoms are prevalent in widows and widowers during the first 2 years of bereavement, with a particular high risk for individuals with a history of depression (53,54).…”
Section: Psychobiology Of Bereavement From the Perspective Of Social mentioning
confidence: 90%
“…Stress activates a number of physiological processes (e.g., autonomic nervous system, immune system), which may have played a role in affective attention and memory in this sample. Indeed, ELS has recently been linked to greater behavioral sensitivity to inflammation (Kuhlman et al, 2020). Additionally, HPA axis functioning and reactivity is robustly modulated by gonadal hormones such as estrogens and testosterone (Heck & Handa, 2019).…”
Section: Discussionmentioning
confidence: 99%